PENGARUH PUPUK KOMPOS, BIOCHAR DAN MOL TERHADAP PRODUKSI TANAMAN JAGUNG PADA TANAH PODSOLIK MERAH KUNING - D, Rahmad; Nurul, Nurul; Nurmiaty, Nurmiaty (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
The development of corn plants (Zea mays L) can be carried out in the soil of Podsolik Merah Kuning. Constraints of organic matter content and low nutrient content so that the production produced is less than optimal. The purpose of this study is to find out the effect of compost, biochar and MOL on the growth and production of corn plants planted in the soil of Podsolik Merah Kuning.The research was prepared in the form of a Group Random Design (RAK) consisting of 5 treatments, namely chemical fertilizers, compost fertilizers and biochar., compost fertilizers and MOL., and compost fertilizers, biochar and MOL. The results showed that the compost fertilizer treatment gave the best results for plant height, which was 176.50 cm, stem diameter 2.56 cm, and fruit weight 106.08 grams. The treatment of compost and MOL gave the best results on the number of leaves as many as 11.08 sheets. The treatment of compost and biochar fertilizers gave the best results at a biomass weight of 430.83 grams. The combination treatment of compost, biochar and MOL gave the best results for the weight of seeds per cob of 167.33 grams, the weight of cobs of 62.00 grams, and the production per hectare of 11.95 tons/ha. The application of compost, biochar, and MOL has an intangible effect on the weight of fruit, seed weight per cob, cob weight and production per hectare but has a real effect on plant height, number of leaves, stem diameter and biomass weight. The application of compost, biochar, and MOL fertilizers tends to provide higher yields for the growth and production of maize plants planted in the Podsolik Merah Kuning soil